Regulation of ATP-binding Cassette Transporters and Cholesterol Efflux by Glucose in Primary Human Monocytes and Murine Bone Marrow-derived Macrophages - Spartano, N. L.; Lamon-Fava, S.; Matthan, N. R.; Ronxhi, J.; Greenberg, A. S.; Obin, M. S.; Lichtenstein, A. H. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Individuals with type 2 diabetes mellitus are at increased risk of developing atherosclerosis. This may be partially attributable to suppression of macrophage ATP-binding cassette (ABC) transporter mediated cholesterol efflux by sustained elevated blood glucose concentrations. 2 models were used to assess this potential relationship: human monocytes/leukocytes and murine bone marrow-derived macrophages (BMDM).10 subjects (4 F/6 M, 50–85 years, BMI 25–35 kg/m²) underwent an oral glucose challenge. Baseline and 1- and 2-h post-challenge ABC-transporter mRNA expression was determined in monocytes, leukocytes and peripheral blood mononuclear cells (PBMC). In a separate study, murine-BMDM were exposed to 5 mmol/L D-glucose (control) or additional 20 mmol/L D- or L-glucose and 25 ug/mL oxidized low density lipoprotein (oxLDL). High density lipoprotein (HDL)-mediated cholesterol efflux and ABC-transporter (ABCA1 and ABCG1) expression were determined.Baseline ABCA1and ABCG1 expression was lower (>50%) in human monocytes and PBMC than leukocytes (p<0.05). 1 h post-challenge leukocyte ABCA1 and ABCG1 expression increased by 37% and 30%, respectively (p<0.05), and began to return to baseline thereafter. There was no significant change in monocyte ABC-transporter expression. In murine BMDM, higher glucose concentrations suppressed HDL-mediated cholesterol efflux (10%; p<0.01) without significantly affecting ABCA1 and ABCG1 expression. Data demonstrate that leukocytes are not a reliable indicator of monocyte ABC-transporter expression.Human monocyte ABC-transporter gene expression was unresponsive to a glucose challenge. Correspondingly, in BMDM, hyperglycemia attenuated macrophage cholesterol efflux in the absence of altered ABC-transporter expression, suggesting that hyperglycemia, per se, suppresses cholesterol transporter activity. This glucose-related impairment in cholesterol efflux may potentially contribute to diabetes-associated atherosclerosis.
Keywords: atherosclerosis; mononuclear cells; leukocytes; hyperglycemia